Identification of Key Actors in the Conservation of Amorphophallus gigas in North Sumatra Using the MACTOR Method - Ridahati Rambey; Rahmawaty; Abdul Rauf; Esther Sorta Mauli Nababan; Mohd Hasmadi Ismail; Mohd Nazip Suratman (Jurnal Sylva Lestari, 2026)
Indonesia’s tropical forests harbor exceptional plant diversity; however, rising global demand for forest-based commodities is intensifying extraction and increasing the risk of extinction. In North Sumatra, Amorphophallus gigas persists within community-managed agroforestry understorey systems, yet a surge in tuber demand since 2019 has accelerated harvesting and expanded trade networks from local collectors to export markets. These pressures threaten the species and highlight the need to identify and coordinate key actors in governing sustainable harvesting and habitat management. This study applies a prospective mixed qualitative–quantitative approach, combining in-depth interviews with farmers, village authorities, collectors, government agencies, academics, non-governmental organizations, industry representatives, and exporters. The MACTOR method was used to assess actor influence and dependence and to map convergence and divergence across three objectives: species conservation, agroforestry habitat protection, and income-oriented cultivation. Results indicate that the Center for Conservation of Natural Resources (BBKSDA) North Sumatra is the most influential and least dependent actor, while farmers remain highly dependent despite managing most habitats on private land. Habitat protection is the most mobilizing objective but shows substantial divergence, reflecting unresolved trade-offs between conservation and cultivation. These findings underscore governance imbalances and the need for inclusive, adaptive strategies, including farmer incentives, capacity building, formalized harvesting rules, and synergies between ex situ conservation and sustainable agroforestry. Keywords: actor, Amorphophallus gigas, conservation, MACTOR, Sustainability